2020
DOI: 10.13075/ijomeh.1896.01411
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of molybdenum compounds in nanosized forms under <i>in vitro</i> and <i>in vivo</i> conditions

Abstract: Nanoparticles of transition metal dichalcogenides, particularly of molybdenum (Mo), have gained a lot of focus due to their exceptional physicochemical properties and the growing number of technological applications. These nanoparticles are also considered as potential therapeutic tools, biosensors or drug carriers. It is crucial to thoroughly examine their biocompatibility and ensure safe usage. The aim of this review is to analyze the available data on the biological effects of different nanoforms of element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 64 publications
1
13
0
1
Order By: Relevance
“…Several studies have suggested that ROS generation and oxidative stress production may be one of the underlying mechanisms, leading to nanoparticle-induced cytotoxicity in different cell types [37][38][39][40]. We analyzed the formation of reactive oxygen species in response to MoS 2 , and found a significant production of ROS in cells at higher doses of MoS These results are also correlated with our result of the cytotoxic effect of particles and could be the cause of cell death seen at higher doses.…”
Section: Effect Of Mos 2 On the Production Of Ros In A549 Cellssupporting
confidence: 86%
“…Several studies have suggested that ROS generation and oxidative stress production may be one of the underlying mechanisms, leading to nanoparticle-induced cytotoxicity in different cell types [37][38][39][40]. We analyzed the formation of reactive oxygen species in response to MoS 2 , and found a significant production of ROS in cells at higher doses of MoS These results are also correlated with our result of the cytotoxic effect of particles and could be the cause of cell death seen at higher doses.…”
Section: Effect Of Mos 2 On the Production Of Ros In A549 Cellssupporting
confidence: 86%
“…Like Silicon and graphene, it has applications in biosensing, and optical sensors but the most important ones are those related to bio-applications like DNA, cancer, and Corona Virus detection [20][21][22][23]. While Silicon and graphene were still under study in their compatibility with human bodies, a study, in [24], showed that MoS 2 may be very effective in curing cancer and Alzheimer's disease. It also showed that the compound has no biological interaction which makes it safe for injection in human bodies.…”
Section: Introductionmentioning
confidence: 99%
“…According to several animal studies, high quantities of Mo have interfered with copper metabolism in animals, causing a change in their typical hematological profile, according to several animal studies 74 . Sobańska et al 75 established that the NPs might induce a protective reaction in the cells, stimulating the antioxidative response and reducing its toxic effect. Hence, the low cytotoxicity would be a matter of complicated cellular balance 76 .…”
Section: Discussionmentioning
confidence: 99%